A randomised controlled trial of CPAP versus non-invasive ventilation for initial treatment of obesity hypoventilation syndrome. Issue 5 (15th November 2016) - Howard, Mark E; Piper, Amanda J; Stevens, Bronwyn; Holland, Anne E; Yee, Brendon J; Dabscheck, Eli; Mortimer, Duncan; Burge, Angela T; Flunt, Daniel; Buchan, Catherine; Rautela, Linda; Sheers, Nicole; et al.
Abstract : Background: Obesity hypoventilation syndrome (OHS) is the most common indication for home ventilation, although the optimal therapy remains unclear, particularly for severe disease. We compared Bi-level and continuous positive airways pressure (Bi-level positive airway pressure (PAP); CPAP) for treatment of severe OHS. Methods: We conducted a multicentre, parallel, double-blind trial for initial treatment of OHS, with participants randomised to nocturnal Bi-level PAP or CPAP for 3 months. The primary outcome was frequency of treatment failure (hospital admission, persistent ventilatory failure or non-adherence); secondary outcomes included health-related quality of life (HRQoL) and sleepiness. Results: Sixty participants were randomised; 57 completed follow-up and were included in analysis (mean age 53 years, body mass index 55 kg/m 2, PaCO2 60 mm Hg). There was no difference in treatment failure between groups (Bi-level PAP, 14.8% vs CPAP, 13.3%, p=0.87). Treatment adherence and wake PaCO2 were similar after 3 months (5.3 hours/night Bi-level PAP, 5.0 hours/night CPAP, p=0.62; PaCO2 44.2 and 45.9 mm Hg, respectively, p=0.60). Between-group differences in improvement in sleepiness (Epworth Sleepiness Scale 0.3 (95% CI -2.8, 3.4), p=0.86) and HRQoL (Short Form (SF)36-SF6d 0.025 (95% CI -0.039, 0.088), p=0.45) were not significant. Baseline severity of ventilatory failure (PaCO2 ) was the only significant predictor of persistent ventilatory failure at 3 months (OR 2.3, p=0.03). Conclusions: In newly diagnosed severe OHS, Bi-level PAP and CPAP resulted in similar improvements in ventilatory failure, HRQoL and adherence. Baseline PaCO2 predicted persistent ventilatory failure on treatment. Long-term studies are required to determine whether these treatments have different cost-effectiveness or impact on mortality. Trial registration number: ACTRN12611000874910, results.